Extraction, Isolation, and Characterization of Nanocrystalline Cellulose from Barangan Banana (Musa acuminata L.) Peduncles Waste - Ratna Ratna; Agus Arip Munawar; Sri Aprilia; Nasrul Arahman (Indonesian Journal of Chemistry, 2023)
Microwave-assisted acid hydrolysis has an impact on the characteristics of nanocrystalline cellulose (NCCs). In this study, NCCs was prepared from banana peduncles through hydrolysis of sulfuric acid (concentrations of 1, 2, and 3 M) and hydrolysis time (0.5 and 1.5 h) assisted by microwave and ultrasonic energy to obtain the best NCCs. The characterization of NCCs properties, namely, yield, morphology, functional groups, crystallinity, heat resistance, particle size, and color. The results showed that the yield of NCCs decreased as sulfuric acid concentration and the time length of hydrolysis increased. The FTIR spectra of NCCs showed the most relevant molecular bands, namely O–H, C–H, and C–O, at the wavenumbers range of 3200–4000, 2500–3200, and 500–1500 cm−1, respectively. The TGA test showed that the decomposition of NCCs occurred at a temperature of 275.35–409.40 °C, with a weight loss ranging from 84.00% to 94.09%. Crystallinity index and crystal sizes range from 53.99% to 57.33% and 22.35 to 36.28 nm, respectively. The brightest color of NCCs powder was generated with 1 M sulfuric acid and a hydrolysis time of 0.5 h. In conclusion, barangan banana peduncles waste can be used as raw material for producing NCCs.